Modelling the impacts of maize decomposition on glyphosate dynamics in mulch. (6th February 2014) - Aslam, S.; Benoit, P.; Chabauty, F.; Bergheaud, V.; Geng, C.; Vieublé‐Gonod, L.; Garnier, P.
Summary The retention of crop residues as mulch on the soil surface in conservation agriculture systems greatly influences the fate of pesticides, as most of the applied pesticide is intercepted by mulch before moving to the soil. This work was conducted in order to model the effect of maize decomposition on glyphosate degradation in mulch and soil. Labelled 14C‐glyphosate degradation was monitored for 49 days in three treatments with the same soils but with maize residues at different stages of decomposition (0, 20 and 49 days). Fresh residues of maize (0 days) exhibited an evolution of their biochemical fractions to a greater extent than decomposed residues. Glyphosate mineralization was faster in the 0‐day treatment in mulch residues and in the soil layer below the mulch. However, a greater formation of non‐extractable residues (NERs) was observed in mulch residues and soils in the 20‐ and 49‐day treatments than in the 0‐day treatment. Modelling maize mulch decomposition with the COP‐soil model indicated that microbial activity was different in the three treatments and depended on the initial composition of maize residues. Glyphosate mineralization in mulch and soil can be simulated with an assumption of co‐metabolism by coupling the modules of pesticide degradation and mulch carbon decomposition. Glyphosate and its metabolites, including soluble and adsorbed fractions, were simulated with the same adsorption coefficients for all treatments. The simulation of NER formation, however, suggested that more than one microbial population may be involved in the degradation process and could be added in the future development of the model.